2016
DOI: 10.1016/j.celrep.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Macroautophagy Proteins Control MHC Class I Levels on Dendritic Cells and Shape Anti-viral CD8 + T Cell Responses

Abstract: The macroautophagy machinery has been implicated in MHC class II restricted antigen presentation. Here, we report that this machinery assists in the internalization of MHC class I molecules. In the absence of the autophagy factors Atg5 and Atg7, MHC class I surface levels are elevated due to decreased endocytosis and degradation. Internalization of MHC class I molecules occurs less efficiently if AAK1 cannot be recruited via Atg8/LC3B. In the absence of Atg-dependent MHC class I internalization, dendritic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 43 publications
5
127
4
Order By: Relevance
“…52 However, AP2 components were not significantly reduced in immunoprecipitates of classical MHC class I molecules derived from Atg5-deficient cells compared with floxed littermates. Instead, Atg5-deficiency compromised MHC class I association with the AP2-associated kinase 1 which can support AP2-independent, but clathrin-dependent endocytosis pathways.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…52 However, AP2 components were not significantly reduced in immunoprecipitates of classical MHC class I molecules derived from Atg5-deficient cells compared with floxed littermates. Instead, Atg5-deficiency compromised MHC class I association with the AP2-associated kinase 1 which can support AP2-independent, but clathrin-dependent endocytosis pathways.…”
Section: Discussionmentioning
confidence: 98%
“…Instead, Atg5-deficiency compromised MHC class I association with the AP2-associated kinase 1 which can support AP2-independent, but clathrin-dependent endocytosis pathways. [52][53][54] Furthermore, LIR motifs have also been described in clathrin itself. 55 Thus, autophagy proteins appear to affect different clathrin-dependent pathways for the internalization and degradation of classical and nonclassical MHC class I molecules, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…246,248 In the case of human cancer xenografts in mice, 75 mg/kg CQ had an immunostimulatory effect, especially once the Treg cells were depleted by the addition of cyclophosphamide. 250 In an experimental system of irradiated human bone marrow cells, 40 lM CQ and a stabilized derivative of cyclophosphamide were sufficient to stimulate elimination of contaminating B-cell acute lymphoblastic leukemia cells by a selective B-cell-directed antibody coupled to an immunotoxin. 60 CQ also prevents the clearance of apoptotic cells by macrophages.…”
Section: Impact Of Cq On Antitumor Immune Responsesmentioning
confidence: 99%
“…These findings suggest that the proinflammatory environment in IBM muscle promotes induction of autophagy in myofibers and subsequently enhances surface MHC class II, thereby maintaining CD4 + T cell infiltrates via the presentation of yet unknown self‐peptides. Intracellular antigen presentation via MHC class I molecules is also regulated by the autophagy machinery, because autophagy‐related proteins enhance MHC class I internalization for degradation and thereby diminish antigen display on the cell surface 268. Indeed, in vivo studies have primarily found enhanced CD8 + T cell responses in mice with defective autophagy in antigen‐presenting cells268, 269, 270 A potential mechanism leading to such increased CD8 + T cell expansions is that, in the absence of autophagy, more substrate becomes available for canonical MHC class I loading271 or by decreased endocytosis and degradation of cell surface MHC class I molecules 268.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 99%